Developing and validating a national logistics cost in Thailand. (August 2022) - Banomyong, Ruth; Grant, David B.; Varadejsatitwong, Paitoon; Julagasigorn, Puthipong
Abstract: National logistics cost can be used as a key indicator to reflect a country's overall logistics performance and monitor their respective logistics policies. However, not all countries have developed this indicator, and some have used differing methodologies. This paper provides an approach for calculating national logistics cost per gross domestic product (NLC/GDP) in the context of Thailand and demonstrates its veracity and validity using an action research methodology with key stakeholders. The approach utilizes easily obtainable macro level data combined with survey data. The calculation method has progressively improved in its accuracy and efficacy to reflect Thailand's logistic context. The proposed approach contributes to the national logistics cost debate and can inform academics, managers, and policy makers not just in Thailand but, in other countries when developing their own NLC/GDP to evaluate their respective logistics development activities. Highlights: Explains methodology to calculate national logistics cost based on national accounts tables and survey. Improves accuracy of national logistics costs calculation. Validates calculation assumptions with empirical survey of 6000 firms. Confirms individual cost components from previous research. National logistics cost can be used for Thai government's logistics policy development.